Macmillan first dictionary - Levey, Judith S., 1936- (New York : Maxwell Macmillan International Pub. Group, 1990)
An alphabetical list of nearly 2200 common words with meanings, explanatory sentences, and illustrations for those words considered "conceptual.".
"Ages 5 to 9"--Backcover.
Booklist.
Elem. School Library Collection.
Wilson's Children.
2.5.
2.5
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries; English language -- Dictionaries